2013
DOI: 10.1021/jz400113y
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and Molecular Liquids: Working Together for Robust Engineering

Abstract: Because of their outstanding versatility, room-temperature ionic liquids (RTILs) are utilized in an ever increasing number of novel and fascinating applications, making them the Holy Grail of modern materials science. In this Perspective, we address the fundamental research and prospective applications of RTILs in combination with molecular liquids, concentrating on three significant areas: (1) the use of molecular liquids to decrease the viscosity of RTILs; (2) the role of RTIL micelle formation in water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 119 publications
2
113
0
Order By: Relevance
“…The heat capacities at T = 298.15 K of the extended se- 4,6,8,10,12,14,16,18,20) ionic liquids were measured by a high-precision heat capacity drop calorimeter, which is described in detail in the literature. [22][23][24] The calorimeter, was originally developed and used at the Thermochemistry Laboratory, Lund, Sweden, 22,23 being afterwards transferred to Porto, Portugal, where it was reassembled, modernized, and tested.…”
Section: A High-precision Heat Capacity Drop Calorimetrymentioning
confidence: 99%
See 3 more Smart Citations
“…The heat capacities at T = 298.15 K of the extended se- 4,6,8,10,12,14,16,18,20) ionic liquids were measured by a high-precision heat capacity drop calorimeter, which is described in detail in the literature. [22][23][24] The calorimeter, was originally developed and used at the Thermochemistry Laboratory, Lund, Sweden, 22,23 being afterwards transferred to Porto, Portugal, where it was reassembled, modernized, and tested.…”
Section: A High-precision Heat Capacity Drop Calorimetrymentioning
confidence: 99%
“…[1][2][3] The possible use of ionic liquids (ILs) as heat transfer for heat exchange in chemical plants and solar thermal power generation was discussed, and it was found that the imidazolium based ionic liquids present higher heat capacities per unit of volume that two high performance commercial thermal fluids. [4][5][6] The knowledge of the heat capacity is required for the evaluation of the applicability of the ionic liquids as heat transfer fluids. [4][5][6] During the past decade, the research in ionic liquids has gained popularity, mainly due to their particular properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Room-temperature ionic liquids (RTILs) [1][2][3][4][5][6][7][8][9][10][11] constitute an active research field.…”
Section: Introductionmentioning
confidence: 99%